Clinicodemographic Characteristics of Cutaneous Larva Migrans: A 10-year Study In Tertiary Referral Hospital-West Java, Indonesia - Avissa, Tuesi Fredella; Gunawan, Hendra; Hidayah, Risa Miliawati Nurul (Journal of General - Procedural Dermatology and Venereology Indonesia, 2022)
Background: Cutaneous larva migrans (CLM) is the most common helminthic dermatosis caused by animal hookworm, commonly reported in tropical and subtropical regions. Most studies are on travellers returning from endemic areas, paradoxically very few reports in endemic countries, including Indonesia, where they mostly take place. This study aimed to describe the demographic and clinical characteristics of CLM patients for 10 years in a tertiary referral hospital in West Java, Indonesia. Methods: This was a descriptive retrospective cross-sectional study. The data were obtained from the medical record of patients who was diagnosed as CLM in Tropical Dermatology Clinic Hasan Sadikin Hospital Bandung from 1st January 2010 until 31st December 2019 using a total sampling method. Results: Of the 21 data retrieved, males (52.4%), age group of 35-44 years (23.8%), senior high school graduated (23.8%), and had a history of vacation to the beach (9.5%) comprised the majority of the patients. The most common clinical characteristics were multiple itchy serpiginous track lesion, located on the arm and hand, and treated with albendazole at 400 mg per day for 3 days showed the cure rate of CLM patients was high (100%). Conclusion: Patients with CLM have a variety characteristics based on clinico-demography. Although CLM is rare in this study, health information about this disease to community is important, especially those who frequently travelled to the endemic regions.